1999
DOI: 10.1016/s0014-5793(99)00460-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of UCP3 by nucleotides is different from regulation of UCP1

Abstract: UCP3 is an isoform of UCP1, expressed primarily in skeletal muscle. Functional properties of UCP3 are still largely unknown. Here, we report about the expression of UCP3 and of UCP1 in inclusion bodies of Escherichia coli. On solubilization and reconstitution into proteoliposomes, both UCP3 and UCP1 transport Cl 3 at rates equal to the reconstituted native UCP1. Cl 3 transport is inhibited by low concentrations of ATP, ADP, GTP and GDP. However, no H + transport activity is found possibly due to the lack of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
2
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 23 publications
6
38
2
2
Order By: Relevance
“…We have also demonstrated that ADP is a slightly stronger UCP2 inhibitor than ATP. The same finding has previously been reported for UCP3 (58). GTP and GDP exhibited a slightly lower inhibitory ability.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We have also demonstrated that ADP is a slightly stronger UCP2 inhibitor than ATP. The same finding has previously been reported for UCP3 (58). GTP and GDP exhibited a slightly lower inhibitory ability.…”
Section: Discussionsupporting
confidence: 90%
“…We must admit that sulfate used in our assay media strongly decreases the PN affinity to UCP1 (25) and presumably also to UCP2/UCP3, which might explain the discrepancies between our K i values and those measured by Klingenberg and co-workers (21,58) and partly also between the K i values (Table II) (Table III). We chose sulfate to ensure that the anion used would be membrane impermeant, would not quench the SPQ probe, and that UCPs would not transport it.…”
Section: Discussionmentioning
confidence: 57%
“…UCP1 is fully inhibited by millimolar concentrations of nucleotides (38), and it has been reported that homologues of UCP1 share this property (13,24,39,40). The inability of GDP to inhibit proton conductance in UCP2high yeast mitochondria is in agreement with evidence from mammalian mitochondria.…”
Section: Effect Of Supraphysiological Concentrations Of Ucp2 On Protosupporting
confidence: 76%
“…7 for a more detailed review). Studies on protontranslocating activities of UCP2 (and UCP3) have, so far, been limited to mitochondrial and proteoliposome systems (9,(18)(19)(20). Thus, the potential of UCP2 to uncouple respiration in intact mammalian cells has not been addressed.…”
Section: Discussionmentioning
confidence: 99%